Using video reflexive ethnography to explore the use of variable rate intravenous insulin infusions - Mais Iflaifel; Rosemary Lim; Clare Crowley; Francesca Greco; Rick Iedema (BMC, 2022)
Abstract Background The use of variable rate intravenous insulin infusion (VRIII) is a complex process that has consistently been implicated in reports of error and consequent harm. Investment in patient safety has focused mainly on learning from errors, though this has yet to be proved to reduce error rates. The Resilient Health Care approach advocates learning from everyday practices. Video reflexive ethnography (VRE) is an innovative methodology used to capture everyday practices, reflect on and thereby improve these. This study set out to explore the use of VRIIIs by utilising the VRE methodology. Methods This study was conducted in a Vascular Surgery Unit. VRE methodology was used to collect qualitative data that involved videoing healthcare practitioners caring for patients treated with VRIII and discussing the resulting clips with participants in reflexive meetings. Transcripts of these were subjected to thematic analysis. Quantitative data (e.g. blood glucose measurements) were collected from electronic patient records in order to contextualise the outcomes of the video-observed tasks. Results The use of VRE in conjunction with quantitative data revealed that context-dependent adaptations (seeking verbal orders to treat hypoglycaemia) and standardised practices (using VRIII guidelines) were strategies used in everyday work. Reflexive meetings highlighted the challenges faced while using VRIII, which were mainly related to lack of clinical knowledge, e.g. prescribing/continuing long-acting insulin analogues alongside the VRIII, and problems with organisational infrastructure, i.e. the wireless blood glucose meter results sometimes not updating on the electronic system. Reflexive meetings also enabled participants to share the meanings of the reality surrounding them and encouraged them to suggest solutions tailored to their work, for example face-to-face, VRIII-focused training. Conclusions VRE deepened understanding of VRIII by shedding light on its essential tasks and the challenges and adaptations entailed by its use. Future research might focus on collecting data across various units and hospitals to develop a full picture of the use of VRIIIs.